Pengaruh Kualitas Pelayanan, Brand Ambassador dan Brand Image Terhadap Kepuasan Konsumen Dengan Brand Image Sebagai Variabel Moderating (Studi Kasus di J&T Cipinang Muara) - Hermansyah, Hermansyah; Alamsyah, Riky (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The rise in online shopping among Indonesian society has driven the growth of the logistics sector, particularly in parcel delivery services. J&T Express is a parcel delivery company that had the largest shipment volume in 2022 and achieved the highest Top Brand recognition in 2023. J&T Express must continue to grow and develop to avoid being surpassed by other logistics service companies. One way to develop a good strategy is by understanding the factors that influence customer satisfaction with the service. Previous research has identified several factors influencing customer satisfaction, including service quality, brand ambassador, and brand image. The number of respondents in this study was 150, all of whom had used J&T Express services. The method used in this research is Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The results of this study indicate that service quality and brand image have a positive and significant effect on customer satisfaction. On the other hand, the brand ambassador does not have a positive and significant effect on customer satisfaction.